PERSEPSI DAN MOTIVASI WISATAWAN YANG BERKUNJUNG KE DAYA TARIK WISATA JEMBONG DI KABUPATEN BULELENG - Anggela, Martina Minnie; Oka Karini, Ni Made; Sofia Wijaya, Ni Made (Jurnal IPTA (Industri Perjalanan Wisata), 2018)
The aim of this research is to determine the tourist perceptions and motivation that visit to Jembong tourist destination. This research was conducted at the Jembong tourist destination, Jembong District, Ambengan Village, Sukasada District, Buleleng Regency. The research method used is descriptive quantitative by distributed questionnaires to two hundred and twenty fivetourist that visiting Jembong tourist destination in Jembong district, Ambengan Village. A questionnaire consisted of twenty threestatements that refer to the theory of tourism development, which are tourist attraction, amenities, access and ancillary services and eighteen statements of tourist motivation that refer to the push and pull theory motivation. The potential tourist attraction in Jembong tourist destination are waterfall, trekking, and nature. The facilities are bathroom and change room, trash bin, restaurant, parking area, and gazebo. Local community who has an authority to make signboard and provided stairs and trail to facilitate tourists toward waterfall and trekking. Tourist information center made simultaneously with entrance ticket counter Jembong tourist destination. Promotion media at Jembong tourist destination are brochure, email and instagram. Maps of Jembong tourist destination is available in google maps therefore tourist easier toward Jembong tourist destination. The results of this research finding the higher of push motivation and pull motivation is related with beauty nature that suitable with the higher tourist perception to attraction are freshness air and beauty nature in Jembong tourist destination.